ISLAMIC EDUCATION CURRICULUM USING PUZZLE MEDIA TO ENHANCE PLAYGROUP STUDENTS' ABILITY TO RECOGNIZE HIJAIYAH LETTERS - Aziz, Mursal; Napitupulu, Dedi Sahputra; Pratiwi, Ira (Al Hikmah Indonesian Journal of Early Childhood Islamic Education, 2024)
Recognizing hijaiyah letters in early childhood should be able to create fun learning activities, one of which is by using hijaiyah letter puzzle media. The aim of this research is to describe Puzzle Media in improving the ability to recognize hijaiyah letters in play group students. This research method uses classroom action research methods. This research was conducted at KB Kasih Anggun North Labuhanbatu. The results of the research, namely the pre-cycle results, show that children's ability to recognize hijaiyah letters using puzzle media in KB Kasih Anggun out of 14 children who got a classical completeness score (KK), namely 9 children (64.28% of 14 children), who got a score below classical. namely 5 children (35.72% of 14 children). The average score in the pre-cycle was 64.28%, so the ability of efforts to increase the recognition of hijaiyah letters in puzzle media in the pre-cycle completion carried out conventionally showed that 35.72% of all students had not yet completed the introduction of hijaiyah letters. The percentage value in cycle I consisting of 14 children reached a value of 57.29%. So the second cycle of action researchers. Based on the results of interviews and observations of KB Kasih Anggun students, the students' learning outcomes had reached KK and resulted in an increase of 75.42%, it was concluded that in this learning the teacher had used puzzle media, so that students could be active in the learning process.